Role of target resonances in low-energy nucleon and a interactions with Weakly-Bound Nuclei - Amos, K.; Karataglidis, S.; Van Der Knijff, D.; Fraser, P.; Kym, M.; Bray, Igor; Kadyrov, Alisher; Canton, L.; Fossión, R.; Svenne, J. (2016)
© Copyright owned by the author(s). Radioactive ion beams of weakly bound nuclei are now being used to investigate properties of nuclear systems well off of the valley of stability. Those ions can and do have low excitation spectra that involve particle unstable resonances. We seek to describe the spectra of the compound systems formed, and the low energy scattering cross sections for clusters formed coupling a nucleon or an a-particle with such weakly bound systems.